High School Students’ Multiple Representation Translation Skills on One-Dimensional Motion: A Cross-Grade Study - Zeynep Başkan Takaoğlu (Universitas Pendidikan Indonesia, 2024)
Multiple representations are widely recognized for their significant role in concept learning. This study aimed to investigate the multiple representation translation skills of high school students at different grade levels about the concept of one-dimensional motion. 239 9th, 10th, and 11th-grade students participated in the study using a developmental research model. The data collection tool consisted of questions that required translating figures, tables, graphs, verbal explanations, and algebraic representations into other representation types in a multiple-representation translation test focusing on one-dimensional motion. Data analysis involved evaluating the translation among representations for each category and analyzing the multiple representation translation skills across different grade levels using one-way analysis of variance (ANOVA). The results revealed that students successfully translated from figure, table, and graphical representations to other forms while encountering challenges in translation from verbal and algebraic representations. Furthermore, the ANOVA results indicated a significant difference between the 9th and 11th grades, favoring the 11th grade.